Acute fatty liver of pregnancy and diagnosis by computed tomography. Issue 6516 (1st February 1986) - McKee, C M; Weir, P E; Foster, J H; Murnaghan, G A; Callender, M E
Abstract : A 39 year old woman was admitted to a maternity unit at 34 weeks' gestation with nausea, vomiting, and jaundice. Her condition deteriorated, and she was transferred to hospital, deeply unconscious and hypotensive. The diagnosis of acute fatty liver of pregnancy was initially suggested by the typical history of prodromal malaise and vomiting and the rapid onset of hepatic encephalopathy with profound hypoglycaemia and only small increases in transaminase activities. Computed tomography was performed: there was no enlargement of the liver or spleen, but the attenuation value over the liver indicated appreciable fatty infiltration of the liver, establishing the diagnosis of acute fatty liver of pregnancy. Computed tomography is of value in the diagnosis of liver disease of late pregnancy, and this technique may become the method of choice for the investigation of acute fatty liver of pregnancy.